Penerapan Green Economy dalam Budi Daya Melon di Desa Plancungan - Dhea Amanda Febriana Putri; Choirul Daroji (Niqosiya: Journal of Economics and Business Research, 2026)
This study examines the implementation of the green economy concept in melon cultivation in Plancungan Village using a descriptive qualitative approach. The research is significant because the agricultural sector faces the challenge of maintaining productivity while ensuring environmental sustainability. The findings indicate that green economy practices are implemented through the use of organic fertilizers, the utilization of rice husks, and proper waste management. Supporting factors include soil fertility and the availability of environmentally friendly agricultural inputs, while inhibiting factors consist of harvest delays and limited access to external training for farmers. The implementation of the green economy generates positive impacts, including a healthier working environment, greater cost efficiency, increased consumer interest, and improved melon production productivity. These findings highlight the potential of green economy practices to support sustainable agricultural development and serve as a reference for the wider adoption of environmentally sustainable farming systems.